Types and severity of physical impairments of para-karate athletes - Augustovicova, D.; Nemcek, D. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Para-karate is applying to be added to the Paralympic Games scheduled to be held in 2028. Research on the classification of para-athletes is common in other para martial arts sports [1,2], however, there is limited research on the classification of para-karate athletes. This study aimed to provide details on the impairments and disabilities of the para-karate players. The secondary objective was to investigate the relationship between the level of impairment and the athletes rankings.